Synthesis and Biological Studies of Salicylhydrazone and their Complexes with Lanthanum - Bajpai, Susmita; Awasthi, Rita (Asian Journal of Chemistry, 2010)
The present study comprises the synthesis of La(III) complexes of salicylhydrazone. All the complexes were characterized by elemental analysis and FT-infrared spectral studies. The biological applications of these compexes are also reported.